2014
DOI: 10.1242/jcs.154518
|View full text |Cite
|
Sign up to set email alerts
|

Functional phylogenetic analysis of LGI proteins identifies an interaction motif crucial for myelination

Abstract: The cellular interactions that drive the formation and maintenance of the insulating myelin sheath around axons are only partially understood. Leucine-rich glioma-inactivated (LGI) proteins play important roles in nervous system development and mutations in their genes have been associated with epilepsy and amyelination. Their function involves interactions with ADAM22 and ADAM23 cell surface receptors, possibly in apposing membranes, thus attenuating cellular interactions. LGI4-ADAM22 interactions are require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Many studies in mammals have defined important regulators of Schwann cell development and myelination, including axonal neuregulin signals and their glial ErbB receptors and key Schwann cell transcription factors including Sox10, Oct6, Brn2, and Krox20 (Jessen and Mirsky 2005;Nave and Salzer 2006;Pereira et al 2012). Analysis of expression patterns, cell behavior, and mutant phenotypes in zebrafish indicates that the functions of these genes are broadly conserved among vertebrates (e.g., Kegel et al 2014;reviewed in Raphael and Talbot 2011).…”
Section: Schwann Cellsmentioning
confidence: 99%
“…Many studies in mammals have defined important regulators of Schwann cell development and myelination, including axonal neuregulin signals and their glial ErbB receptors and key Schwann cell transcription factors including Sox10, Oct6, Brn2, and Krox20 (Jessen and Mirsky 2005;Nave and Salzer 2006;Pereira et al 2012). Analysis of expression patterns, cell behavior, and mutant phenotypes in zebrafish indicates that the functions of these genes are broadly conserved among vertebrates (e.g., Kegel et al 2014;reviewed in Raphael and Talbot 2011).…”
Section: Schwann Cellsmentioning
confidence: 99%
“…Recent work by Kegel et al () has identified a novel mechanism of VGKCs clustering during PNS myelination involving the cell surface receptor ADAM23. We have verified the presence of ADAM23 at the CNS juxtaparanodes of the adult WT as well as Tag‐1 −/− callosal fibers during remyelination, co‐localized with VGKCs (Figure f).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has revealed the existence of an additional molecule at the juxtaparanode, ADAM23, which was found to co‐localize with Caspr2, CNTN2, and VGKCs at the area (Kegel et al, ). It has been suggested that ADAM22 and ADAM23 expression in apposing cell membranes at the juxtaparanode might be an additional mechanism of juxtaparanodal complex organization and/or stability possibly in an LGI4‐dependent manner, although this hypothesis needs further investigation (Kegel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Dorsal root ganglia (DRG) were dissected from mouse embryos at embryonic day 13 or postnatal day 4–6 pups (sex not determined) according to established protocols (Kegel et al, 2014; Kleitman et al, 2002; Sleigh et al, 2016). Cells were seeded as explants onto Matrigel (BD Biosciences)/poly‐D‐lysine (Sigma)‐coated 16 mm coverslips (Thermo Scientific) and maintained in MEM (Gibco) supplemented with 3% Fetal Bovine serum (FBS), 50 ng/ml NGF and Penicillin and Streptomycin (M1 medium) in a 5%CO 2 incubator at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Mice carrying homozygous Lgi4 mutant alleles (the “claw paw” allele Lgi4 Clp or Lgi4 ∆1–3 ) or homozygous Adam22 ( Adam22 ∆ 1 ) mutant alleles have a severely reduced lifespan, exhibit pronounced joint contractures (Bermingham et al, 2006; Darbas et al, 2004; Henry et al, 1991; Nishino et al, 2010; Ozkaynak et al, 2010; Sagane et al, 2005) and congenital hypomyelination of the PNS. Functional studies identified a patch of amino acids within the Epitempin domain of Lgi4 that is crucially involved in promoting myelination but distinct from its Adam22 binding interface (Kegel et al, 2014) (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%